Creativity of Virtual Dance Competition of Ã¢â‚¬Å“Beksan Nir CoronaÃ¢â‚¬Â in The Kraton of Yogyakarta - Kuswarsantyo, Kuswarsantyo; Fitrianto, Otok (Harmonia: Journal of Arts Research and Education, 2020)
The objectives of this study are to: (1) describe and analyze the arrangement tutorial of Beksan Nir Corona on a virtual dance competition in the Kraton of Yogyakarta; and (2) describe and analyze the level of similarity in imitation of movement patterns and creativity in the presentation of the participants in the dance competition of Beksan Nir Corona. The method used in this research is descriptive qualitative supported by percentage descriptive quantitative data. The data collection process was carried out using observation, interview, and document techniques. Data analysis was carried out by the stages of data reduction, data presentation, and drawing conclusions. The research results show that the virtual dance tutorial of Beksan Nir Corona as a competition guide contains a recording of a dance model, which is a stylization of five steps of washing hands into a simple variety of movements in the classical dance of Yogyakarta style. Judges’ assessment results through dance performance videos uploaded by 196 participants showed that: (1) the ability of participants to imitate all movement patterns according to the dance material of Beksan Nir Corona reached 85%; (2) the ability of participants to be creative which is manifested in the ability to express ideas only reached 60%; and (3) the remaining 40% of participants only danced the dance of Beksan Nir Corona by imitating the movement patterns that had been exemplified. The average ability to imitate the movement patterns of the dance of Beksan Nir Corona based on the assessment of the six judges is 85.5. In contrast, the creative ability in dance presentation is 70.5.